Conjuntos numéricos - Duarte, Carlos Eduardo de Lima (2013)
In this work, we present a text on the Sets Numerical using the human social needs as a tool for construction new numbers. This material is intended to present a text that reconciles the correct teaching of mathmatics and clarity needed for a good learning